(untitled) (Journal of Economic Research & Business Administration, 2016)
Logistics – science which subject consists in the organization of ratio nal process of advance of goods and services from suppliers of raw materi als to consumers, functioning of the sphere of the address of production, goods, services, managements of commodity stocks and provisions, cre ations of infrastructure of merchandising. The purchasing logistics is one of the main logistic subsystems. Its common goal can be determined as acquisition of necessary goods of the necessary quality and quantity with delivery in the right place and time from the reliable supplier, with good service and by the favorable price. In article practice of material support of the industrial enterprise is studied showed that most of heads of the en terprises are often not familiar with such term as “logistics”, and especially the tools of logistics in the work are used only by units. In article the es sence of purchasing logistics and its feature in the Republic of Kazakhstan is considered.